Analisis Kualitatif Penanganan Kasus Human Trafficking Berbasis Teknologi (Online Scam) dalam Perspektif Hukum Positif Indonesia - Shafira Azzahra Eka Putri; Aries Isnandar (WELFARE STATE Jurnal Hukum, 2026)
The development of digital technology has driven the emergence of a new modus operandi in human trafficking crimes, namely technology-based human trafficking through online scam schemes. This phenomenon is marked by the recruitment of victims through social media, fake job advertisements, and messaging apps, who are then coerced into committing online fraud under threats, violence, and technological control. The main issue of this research is how Indonesian positive law responds to online scam-based human trafficking practices and to what extent law enforcement can protect victims who experience digital exploitation. This study aims to analyze the adequacy of the national legal framework, the dynamics of crime modus operandi, and the obstacles in cross-border handling. The research method uses a qualitative approach with a socio-legal research type through literature review of regulations, news, and academic research. The research findings show that the online scam practices carried out by the victims fulfill the elements of human trafficking according to Law No. 21/2007 through the concept of forced criminality. However, law enforcement faces challenges such as cross-border jurisdiction, digital evidence, and miscategorization of victims as perpetrators. This study emphasizes the need to strengthen technology-based regulations, improve international cooperation, and establish comprehensive protection mechanisms for the identity and recovery of victims.